Primary Hepatic Lymphoma: A Complex and Challenging Diagnosis - Joshi, Rinku; Singh, Pritanjali; Shrestha, Dhan Bahadur (Medical Journal of Shree Birendra Hospital, 2017)
Primary hepatic lymphoma is the rare condition affecting liver and presents to clinician as space occupying lesion and is an extranodal variety of non-Hodgkin lymphoma. The diagnosis is based on the suspicious eye with keen laboratory investigation after ruling out the other common pathologies of the liver which presents as space occupying lesion. Here we present a case who presented to us with dull pain and swelling right upper abdomen accompanied by prodromal symptoms which after proper work up was diagnosed as primary diffuse large B-cell non-Hodgkin lymphoma (NHL) of liver.